KEPUASAN KERJA MEMEDIASI PENGARUH WORKPLACE SPIRITUALITY DAN RELIGIOSITY TERHADAP KINERJA APARATUR SIPIL NEGARA (STUDI KASUS PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBERDAYA MANUSIA KABUPATEN PESISIR SELATAN) - Ricky Saputra; Herri; Yulihasri (Journal Publicuho, 2024)
This study aims to analyze the effect of Workplace Spirituality, and religiosity on the performance of civil servants with job satisfaction as a mediating variable. This research is quantitative research. This type of research is correlational research. A correlational investigation is an identification of important factors that are "related to" the problem. The study used all state civil apparatus respondents totaling 61 people who worked at the South Coastal Regency Personnel and Human Resources Development Agency. this research technique uses the Census, which means that information collection from all members of the population is used as a sample to collect information. The data collection technique used a questionnaire, while the data analysis used SmartPLS. The results showed that: (1) Workplace Spirituality has a positive and significant effect on Employee Performance, (2) Religiosity has a positive and significant effect on Employee Performance, (3) Workplace Spirituality has a positive and significant effect on Job Satisfaction, (4) Religiosity has a positive and significant effect on Job Satisfaction, (5) Job Satisfaction has a positive and significant effect on employee performance, (6) Job Satisfaction Mediates the effect of Workplace Spirituality on Employee Performance, providing a positive impact and significant influence on employee performance in the context of work discipline, and (7) Job Satisfaction Mediates the effect of Religiosity on Employee Performance.